Is increased time to diagnosis and treatment in symptomatic cancer associated with poorer outcomes? Systematic review - Neal, R D; Tharmanathan, P; France, B; Din, N U; Cotton, S; Fallon-Ferguson, J; Hamilton, W; Hendry, A; Hendry, M; Lewis, R; Macleod, U; Mitchell, E D; et al. (British journal of cancer, 2015)
Background: It is unclear whether more timely cancer diagnosis brings favourable outcomes, with much of the previous evidence, in some cancers, being equivocal. We set out to determine whether there is an association between time to diagnosis, treatment and clinical outcomes, across all cancers for symptomatic presentations. Methods: Systematic review of the literature and narrative synthesis. Results: We included 177 articles reporting 209 studies. These studies varied in study design, the time intervals assessed and the outcomes reported. Study quality was variable, with a small number of higher-quality studies. Heterogeneity precluded definitive findings. The cancers with more reports of an association between shorter times to diagnosis and more favourable outcomes were breast, colorectal, head and neck, testicular and melanoma. Conclusions: This is the first review encompassing many cancer types, and we have demonstrated those cancers in which more evidence of an association between shorter times to diagnosis and more favourable outcomes exists, and where it is lacking. We believe that it is reasonable to assume that efforts to expedite the diagnosis of symptomatic cancer are likely to have benefits for patients in terms of improved survival, earlier-stage diagnosis and improved quality of life, although these benefits vary between cancers.